Factoring Polynomials Chapter 5 Factoring Polynomials
Chapter Sections 13.1 – The Greatest Common Factor 13.2 – Factoring Trinomials of the Form x2 + bx + c 13.3 – Factoring Trinomials of the Form ax2 + bx + c 13.4 – Factoring Trinomials of the Form x2 + bx + c by Grouping 13.5 – Factoring Perfect Square Trinomials and Difference of Two Squares 13.6 – Solving Quadratic Equations by Factoring 13.7 – Quadratic Equations and Problem Solving Chapter 13 Outline
The Greatest Common Factor § 13.1 The Greatest Common Factor
Factors Factors (either numbers or polynomials) When an integer is written as a product of integers, each of the integers in the product is a factor of the original number. When a polynomial is written as a product of polynomials, each of the polynomials in the product is a factor of the original polynomial. Factoring – writing a polynomial as a product of polynomials.
Greatest Common Factor Greatest common factor – largest quantity that is a factor of all the integers or polynomials involved. Finding the GCF of a List of Integers or Terms Prime factor the numbers. Identify common prime factors. Take the product of all common prime factors. If there are no common prime factors, GCF is 1.
Greatest Common Factor Example Find the GCF of each list of numbers. 12 and 8 12 = 2 · 2 · 3 8 = 2 · 2 · 2 So the GCF is 2 · 2 = 4. 7 and 20 7 = 1 · 7 20 = 2 · 2 · 5 There are no common prime factors so the GCF is 1.
Greatest Common Factor Example Find the GCF of each list of numbers. 6, 8 and 46 6 = 2 · 3 8 = 2 · 2 · 2 46 = 2 · 23 So the GCF is 2. 144, 256 and 300 144 = 2 · 2 · 2 · 3 · 3 256 = 2 · 2 · 2 · 2 · 2 · 2 · 2 · 2 300 = 2 · 2 · 3 · 5 · 5 So the GCF is 2 · 2 = 4.
Greatest Common Factor Example Find the GCF of each list of terms. x3 and x7 x3 = x · x · x x7 = x · x · x · x · x · x · x So the GCF is x · x · x = x3 6x5 and 4x3 6x5 = 2 · 3 · x · x · x 4x3 = 2 · 2 · x · x · x So the GCF is 2 · x · x · x = 2x3
Greatest Common Factor Example Find the GCF of the following list of terms. a3b2, a2b5 and a4b7 a3b2 = a · a · a · b · b a2b5 = a · a · b · b · b · b · b a4b7 = a · a · a · a · b · b · b · b · b · b · b So the GCF is a · a · b · b = a2b2 Notice that the GCF of terms containing variables will use the smallest exponent found amongst the individual terms for each variable.
Factoring Polynomials The first step in factoring a polynomial is to find the GCF of all its terms. Then we write the polynomial as a product by factoring out the GCF from all the terms. The remaining factors in each term will form a polynomial.
Factoring out the GCF Example Factor out the GCF in each of the following polynomials. 1) 6x3 – 9x2 + 12x = 3 · x · 2 · x2 – 3 · x · 3 · x + 3 · x · 4 = 3x(2x2 – 3x + 4) 2) 14x3y + 7x2y – 7xy = 7 · x · y · 2 · x2 + 7 · x · y · x – 7 · x · y · 1 = 7xy(2x2 + x – 1)
Factoring out the GCF Example Factor out the GCF in each of the following polynomials. 1) 6(x + 2) – y(x + 2) = 6 · (x + 2) – y · (x + 2) = (x + 2)(6 – y) 2) xy(y + 1) – (y + 1) = xy · (y + 1) – 1 · (y + 1) = (y + 1)(xy – 1)
Factoring Remember that factoring out the GCF from the terms of a polynomial should always be the first step in factoring a polynomial. This will usually be followed by additional steps in the process. Example Factor 90 + 15y2 – 18x – 3xy2. 90 + 15y2 – 18x – 3xy2 = 3(30 + 5y2 – 6x – xy2) = 3(5 · 6 + 5 · y2 – 6 · x – x · y2) = 3(5(6 + y2) – x (6 + y2)) = 3(6 + y2)(5 – x)
Factoring Trinomials of the Form x2 + bx + c § 13.2 Factoring Trinomials of the Form x2 + bx + c
Factoring Trinomials Recall by using the FOIL method that (x + 2)(x + 4) = x2 + 4x + 2x + 8 = x2 + 6x + 8 To factor x2 + bx + c into (x + one #)(x + another #), note that b is the sum of the two numbers and c is the product of the two numbers. So we’ll be looking for 2 numbers whose product is c and whose sum is b. Note: there are fewer choices for the product, so that’s why we start there first.
Factoring Polynomials Example Factor the polynomial x2 + 13x + 30. Since our two numbers must have a product of 30 and a sum of 13, the two numbers must both be positive. Positive factors of 30 Sum of Factors 1, 30 31 2, 15 17 3, 10 13 Note, there are other factors, but once we find a pair that works, we do not have to continue searching. So x2 + 13x + 30 = (x + 3)(x + 10).
Factoring Polynomials Example Factor the polynomial x2 – 11x + 24. Since our two numbers must have a product of 24 and a sum of -11, the two numbers must both be negative. Negative factors of 24 Sum of Factors – 1, – 24 – 25 – 2, – 12 – 14 – 3, – 8 – 11 So x2 – 11x + 24 = (x – 3)(x – 8).
Factoring Polynomials Example Factor the polynomial x2 – 2x – 35. Since our two numbers must have a product of – 35 and a sum of – 2, the two numbers will have to have different signs. Factors of – 35 Sum of Factors – 1, 35 34 1, – 35 – 34 – 5, 7 2 5, – 7 – 2 So x2 – 2x – 35 = (x + 5)(x – 7).
Prime Polynomials Example Factor the polynomial x2 – 6x + 10. Since our two numbers must have a product of 10 and a sum of – 6, the two numbers will have to both be negative. Negative factors of 10 Sum of Factors – 1, – 10 – 11 – 2, – 5 – 7 Since there is not a factor pair whose sum is – 6, x2 – 6x +10 is not factorable and we call it a prime polynomial.
Check Your Result! You should always check your factoring results by multiplying the factored polynomial to verify that it is equal to the original polynomial. Many times you can detect computational errors or errors in the signs of your numbers by checking your results.
Factoring Trinomials of the Form ax2 + bx + c § 13.3 Factoring Trinomials of the Form ax2 + bx + c
Factoring Trinomials Returning to the FOIL method, F O I L (3x + 2)(x + 4) = 3x2 + 12x + 2x + 8 = 3x2 + 14x + 8 To factor ax2 + bx + c into (#1·x + #2)(#3·x + #4), note that a is the product of the two first coefficients, c is the product of the two last coefficients and b is the sum of the products of the outside coefficients and inside coefficients. Note that b is the sum of 2 products, not just 2 numbers, as in the last section.
Factoring Polynomials Example Factor the polynomial 25x2 + 20x + 4. Possible factors of ac=12*4=100 are {10,10} … {5, 20}…etc. The pair that adds up to b= 20 is {10 and 10} We are not done here because I don’t simply have (x+ 10)(x+10). I must keep factoring Continued.
Factoring Polynomials Example Continued We will be factoring out the GCF by groups. First, rewrite the polynomial with your two factors breaking up the x term. 25x2 + 10x + 10x + 4 Then, Find the GCF of the first two terms and then the GCF of the second two terms 5x(5x + 2) + 2(5x + 2) Continued.
Factoring Polynomials Example Continued Then factor out the common binomial. The second binomial is the combination of both GCF’s. 5x(5x + 2) + 2(5x + 2) (5x + 2)(5x + 2) So our final answer when asked to factor 25x2 + 20x + 4 will be (5x + 2)(5x + 2) or (5x + 2)2.
Factoring Polynomials Example Factor the polynomial 21x2 – 41x + 10. Possible factors of ac that add up to b are Factors of 210 that add up to -41 (both negative factors) {-2, -105}, {-5, -42}, {-10, -21}, {-6, -35} , etc… Continued.
Factoring Polynomials Example Continued Split your x term: 21x2 – 35x – 6x + 10 Factor out the GCF: 7x(3x – 5) – 2(3x – 5) Continued.
Factoring Polynomials Example Continued Split your x term: 21x2 – 35x – 6x + 10 Factor out the GCF: 7x(3x – 5) – 2(3x – 5) Answer: (3x – 5)(7x – 2) Continued.
Factoring Polynomials Example Continued Check the resulting factorization using the FOIL method. 3x(7x) F + 3x(-2) O - 5(7x) I - 5(-2) L (3x – 5)(7x – 2) = = 21x2 – 6x – 35x + 10 = 21x2 – 41x + 10 So our final answer when asked to factor 21x2 – 41x + 10 will be (3x – 5)(7x – 2).
Factoring Perfect Square Trinomials and the Difference of Two Squares § 13.5 Factoring Perfect Square Trinomials and the Difference of Two Squares
Perfect Square Trinomials Recall that in our very first example in Section 4.3 we attempted to factor the polynomial 25x2 + 20x + 4. The result was (5x + 2)2, an example of a binomial squared. Any trinomial that factors into a single binomial squared is called a perfect square trinomial.
Perfect Square Trinomials In the last chapter we learned a shortcut for squaring a binomial (a + b)2 = a2 + 2ab + b2 (a – b)2 = a2 – 2ab + b2 So if the first and last terms of our polynomial to be factored are can be written as expressions squared, and the middle term of our polynomial is twice the product of those two expressions, then we can use these two previous equations to easily factor the polynomial. a2 + 2ab + b2 = (a + b)2 a2 – 2ab + b2 = (a – b)2
Perfect Square Trinomials Example Factor the polynomial 16x2 – 8xy + y2. Since the first term, 16x2, can be written as (4x)2, and the last term, y2 is obviously a square, we check the middle term. 8xy = 2(4x)(y) (twice the product of the expressions that are squared to get the first and last terms of the polynomial) Therefore 16x2 – 8xy + y2 = (4x – y)2. Note: You can use FOIL method to verify that the factorization for the polynomial is accurate.
Difference of Two Squares Another shortcut for factoring a trinomial is when we want to factor the difference of two squares. a2 – b2 = (a + b)(a – b) A binomial is the difference of two square if both terms are squares and the signs of the terms are different. 9x2 – 25y2 – c4 + d4
Difference of Two Squares Example Factor the polynomial x2 – 9. The first term is a square and the last term, 9, can be written as 32. The signs of each term are different, so we have the difference of two squares Therefore x2 – 9 = (x – 3)(x + 3). Note: You can use FOIL method to verify that the factorization for the polynomial is accurate.
Solving Quadratic Equations by Factoring § 13.6 Solving Quadratic Equations by Factoring
Zero Factor Theorem Quadratic Equations Zero Factor Theorem Can be written in the form ax2 + bx + c = 0. a, b and c are real numbers and a 0. This is referred to as standard form. Zero Factor Theorem If a and b are real numbers and ab = 0, then a = 0 or b = 0. This theorem is very useful in solving quadratic equations.
Solving Quadratic Equations Steps for Solving a Quadratic Equation by Factoring Write the equation in standard form. Factor the quadratic completely. Set each factor containing a variable equal to 0. Solve the resulting equations. Check each solution in the original equation.
Solving Quadratic Equations Example Solve x2 – 5x = 24. First write the quadratic equation in standard form. x2 – 5x – 24 = 0 Now we factor the quadratic using techniques from the previous sections. x2 – 5x – 24 = (x – 8)(x + 3) = 0 We set each factor equal to 0. x – 8 = 0 or x + 3 = 0, which will simplify to x = 8 or x = – 3 Continued.
Solving Quadratic Equations Example Continued Check both possible answers in the original equation. 82 – 5(8) = 64 – 40 = 24 true (–3)2 – 5(–3) = 9 – (–15) = 24 true So our solutions for x are 8 or –3.
Solving Quadratic Equations Example Solve 4x(8x + 9) = 5 First write the quadratic equation in standard form. 32x2 + 36x = 5 32x2 + 36x – 5 = 0 Now we factor the quadratic using techniques from the previous sections. 32x2 + 36x – 5 = (8x – 1)(4x + 5) = 0 We set each factor equal to 0. 8x – 1 = 0 or 4x + 5 = 0 8x = 1 or 4x = – 5, which simplifies to x = or Continued.
Solving Quadratic Equations Example Continued Check both possible answers in the original equation. true true So our solutions for x are or .
Finding x-intercepts Recall that in Chapter 3, we found the x-intercept of linear equations by letting y = 0 and solving for x. The same method works for x-intercepts in quadratic equations. Note: When the quadratic equation is written in standard form, the graph is a parabola opening up (when a > 0) or down (when a < 0), where a is the coefficient of the x2 term. The intercepts will be where the parabola crosses the x-axis.
Finding x-intercepts Example Find the x-intercepts of the graph of y = 4x2 + 11x + 6. The equation is already written in standard form, so we let y = 0, then factor the quadratic in x. 0 = 4x2 + 11x + 6 = (4x + 3)(x + 2) We set each factor equal to 0 and solve for x. 4x + 3 = 0 or x + 2 = 0 4x = –3 or x = –2 x = –¾ or x = –2 So the x-intercepts are the points (–¾, 0) and (–2, 0).
Quadratic Equations and Problem Solving § 13.7 Quadratic Equations and Problem Solving
Strategy for Problem Solving General Strategy for Problem Solving Understand the problem Read and reread the problem Choose a variable to represent the unknown Construct a drawing, whenever possible Propose a solution and check Translate the problem into an equation Solve the equation Interpret the result Check proposed solution in problem State your conclusion
Finding an Unknown Number Example The product of two consecutive positive integers is 132. Find the two integers. 1.) Understand Read and reread the problem. If we let x = one of the unknown positive integers, then x + 1 = the next consecutive positive integer. Continued
Finding an Unknown Number Example continued 2.) Translate • The product of is = 132 two consecutive positive integers x (x + 1) Continued
Finding an Unknown Number Example continued 3.) Solve x(x + 1) = 132 x2 + x = 132 (Distributive property) x2 + x – 132 = 0 (Write quadratic in standard form) (x + 12)(x – 11) = 0 (Factor quadratic polynomial) x + 12 = 0 or x – 11 = 0 (Set factors equal to 0) x = –12 or x = 11 (Solve each factor for x) Continued
Finding an Unknown Number Example continued 4.) Interpret Check: Remember that x is suppose to represent a positive integer. So, although x = -12 satisfies our equation, it cannot be a solution for the problem we were presented. If we let x = 11, then x + 1 = 12. The product of the two numbers is 11 · 12 = 132, our desired result. State: The two positive integers are 11 and 12.
The Pythagorean Theorem In a right triangle, the sum of the squares of the lengths of the two legs is equal to the square of the length of the hypotenuse. (leg a)2 + (leg b)2 = (hypotenuse)2
The Pythagorean Theorem Example Find the length of the shorter leg of a right triangle if the longer leg is 10 miles more than the shorter leg and the hypotenuse is 10 miles less than twice the shorter leg. 1.) Understand Read and reread the problem. If we let x = the length of the shorter leg, then x + 10 = the length of the longer leg and 2x – 10 = the length of the hypotenuse. Continued
The Pythagorean Theorem Example continued 2.) Translate By the Pythagorean Theorem, (leg a)2 + (leg b)2 = (hypotenuse)2 x2 + (x + 10)2 = (2x – 10)2 3.) Solve x2 + (x + 10)2 = (2x – 10)2 x2 + x2 + 20x + 100 = 4x2 – 40x + 100 (multiply the binomials) 2x2 + 20x + 100 = 4x2 – 40x + 100 (simplify left side) 0 = 2x2 – 60x (subtract 2x2 + 20x + 100 from both sides) 0 = 2x(x – 30) (factor right side) x = 0 or x = 30 (set each factor = 0 and solve) Continued
The Pythagorean Theorem Example continued 4.) Interpret Check: Remember that x is suppose to represent the length of the shorter side. So, although x = 0 satisfies our equation, it cannot be a solution for the problem we were presented. If we let x = 30, then x + 10 = 40 and 2x – 10 = 50. Since 302 + 402 = 900 + 1600 = 2500 = 502, the Pythagorean Theorem checks out. State: The length of the shorter leg is 30 miles. (Remember that is all we were asked for in this problem.)